1999
DOI: 10.1046/j.1365-3040.1999.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of photorespiration during drought stress: an analysis utilizing barley mutants with reduced activities of photorespiratory enzymes

Abstract: The significance of photorespiration in drought-stressed plants was studied by withholding water from wild-type barley (Hordeum vulgare L.) and from heterozygous mutants with reduced activities of chloroplastic glutamine synthetase (GS-2), glycine decarboxylase (GDC) or serine : glyoxylate aminotransferase (SGAT). Wellwatered plants of all four genotypes had identical rates of photosynthesis. Under moderate drought stress (leaf water potentials between -1 and -2 MPa), photosynthesis was lower in the mutants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
157
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(183 citation statements)
references
References 49 publications
(65 reference statements)
16
157
1
2
Order By: Relevance
“…The GS2 mutants of barley has usually normal rates of photosynthesis in moderate light and ambient CO 2 (Häusler et al, 1994a;Wingler et al, 1997); this was confirmed also by our measurements. It was previously shown that the reduced GS activity led often to decrease of CO 2 assimilation and PSII electron transport rate, but mostly in photorespiratory conditions (Häusler et al, 1994a;Wingler et al, 1999;Streb et al, 1998). This was probably the case of our measurements in natural sunlight (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The GS2 mutants of barley has usually normal rates of photosynthesis in moderate light and ambient CO 2 (Häusler et al, 1994a;Wingler et al, 1997); this was confirmed also by our measurements. It was previously shown that the reduced GS activity led often to decrease of CO 2 assimilation and PSII electron transport rate, but mostly in photorespiratory conditions (Häusler et al, 1994a;Wingler et al, 1999;Streb et al, 1998). This was probably the case of our measurements in natural sunlight (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…The supply of glutamine to a GS2 mutant of barley restored photosynthetic activity (Blackwell et al, 1987). However, the pools of RuBP was shown to be almost unaffected by mutation of GS-2 (Leegood et al, 1995;Wingler et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore the integral performance during the whole season is relevant for a comprehensive evaluation of a species or of a genotype. Net photosynthesis does not only depend on photosynthetic electron transport and Calvin cycle activity, since carbon losses via decarboxylation processes also contribute to the overall performance (Wingler et al, 1999;Haupt-Herting et al, 2001;Noctor et al, 2002;Bai et al, 2008;Rivero et al, 2009;Vassileva et al, 2009Vassileva et al, , 2011. The impact of heat and drought on respiration is also crucial for the carbon balance and should be considered when comparing genotypes (Flexas et al, 2006;Vassileva et al, 2011).…”
Section: Net Co2 Assimilationmentioning
confidence: 99%
“…HCR mutants with defects in several of the enzymes of the photorespiratory pathway have been isolated in the C 3 plants Arabidopsis (Somerville and Ogren, 1982) and barley (Hordeum vulgare) (Joy et al, 1992;Leegood et al, 1996;Wingler et al, 1999). These photorespiratory mutants exhibited lethality (HCR phenotype) in air levels of CO 2 for various reasons, including accumulation of toxic intermediates during photorespiration and depletion of exchangeable nitrogen in photorespiratory intermediates.…”
Section: Discussionmentioning
confidence: 99%